2018
DOI: 10.3390/ani8120235
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Goat Production: Enteric Methane Emission and Its Mitigation

Abstract: Simple SummaryGiven that goats are considered more climate resilient than other ruminant species, research efforts are therefore needed to understand goat productivity during exposure to high ambient temperatures. Heat stress can affect the digestion and rumen fermentation pattern of goats, which contributes to the reduction in production performance in goats. Diet composition, breed and environmental stresses are common factors which negatively influence rumen function and enteric methane (CH4) emission. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 91 publications
(126 reference statements)
1
30
0
1
Order By: Relevance
“…Some of their ability to adapt is due to their habit of browsing together with the anatomical advantage of the upper lips. Therefore, goats can thrive well with limited feedstuffs, especially in arid and semiarid regions (Pragna et al 2018). Another advantage is that during feed scarcity, goats can reduce their metabolic processes to conserve energy resource (Yadav et al 2013).…”
Section: Climate Change Impact On Food Availabilitymentioning
confidence: 99%
“…Some of their ability to adapt is due to their habit of browsing together with the anatomical advantage of the upper lips. Therefore, goats can thrive well with limited feedstuffs, especially in arid and semiarid regions (Pragna et al 2018). Another advantage is that during feed scarcity, goats can reduce their metabolic processes to conserve energy resource (Yadav et al 2013).…”
Section: Climate Change Impact On Food Availabilitymentioning
confidence: 99%
“…The small ruminant production system is affected by climate change and contributes to global warming with GHG emissions (Marino et al, 2015). Since goats are considered more climate resilient than other ruminant species (Pragna et al, 2018), their contribution to GHG emissions is more important to highlight. This paper aims to provide an integrated overview on the opportunities to mitigate GHG emissions from sheep and goat farming in Indonesia.…”
Section: Referencesmentioning
confidence: 99%
“…Pragna et al [16] reported that enteric methane can be mitigated through three mechanisms: targeting end products of digestion to propionate, providing alternate hydrogen sinks, and selectively inactivating rumen methanogens. These mechanisms decrease methane production through several strategies: dietary composition (by increasing starch, decreasing cell wall components, and grinding), lipids (fatty acids, oils, seeds, and tallow), defaunation (chemical and feed additives), methanogen vaccine, monensin, plant compounds (condensed tannins, saponins, and essential oils), or organic acids (fumarate or malate) [15].…”
Section: Rumen Microbiota and Enteric Methane Mitigationmentioning
confidence: 99%